Thanatophoric Skeletal Dysplasia Type 2: Diagnostic and Management Dilemmas - Hermawan, Gezta Nasafir; Wibisono, Jacobus Jeno; Velies, Dyana Safitri (Indonesian Socety of Obstetrics and Gynecology, 2023)
Abstract (English) Objective: To report a rare case of thanatophoric skeletal dysplasia type 2 that we diagnosed during prenatal period; and to provide further review of dilemmas in diagnostic methods and management, based on appropriate literatures and guidelines available. Methods: Case report Case: A 33-year old primigravida women was diagnosed with pre-term pregnancy (24th weeks of gestation) and intra-uterine singleton live fetus with thanatophoric skeletal dysplasia type 2 via ultrasonography. Pregnancy termination via elected caesarean section at 26th weeks of gestation was performed per the patient request after considering the fetus’s lethality. A female neonate was born weighing 980 grams with frontal bossing (Head Circumference: 26 cm), lower set of ears, hypertelorism, bilateral exopthalmos, short neck, rhizomelic short extremities, and narrow thorax (Thorax Circumference: 17 cm). The newborn was immediately transferred to NICU for post-natal management and observation. The newborn is in stable condition for the first several hours; nevertheless, significant destabilization occurred afterwards and the newborn deceased approximately 10 hours after birth due to cardiorespiratory failure. No further invasive resuscitative efforts and post-mortem examinations were performed on the parent’s request. Conclusion: Thanatophoric dysplasia is primarily diagnosed using ultrasonography, which has a high detection rate for both diagnosis and prognostications. Even though, There has been a dilemma in performing molecular diagnostic testing, prediction of recurrence risk in future pregnancies can be assessed with its use. Although still remains a challenge in ethical and medicolegal grounds; proper management requires holistic considerations of maternal, fetal, and perinatal aspects. Keywords: Thanatophoric, Skeletal Dysplasia, FGFR3 mutation Abstrak (Indonesia) Tujuan: Melaporkan suatu kasus langka displasia skeletal tanatoforik tipe 2 yang kami diagnosa dalam periode perinatal; serta memberikan ulasan lanjut mengenai dilema dalam metode diagnostik dan manajemen, berdasarkan literatur dan pedoman ilmiah yang tersedia. Metode: Laporan Kasus Kasus: Seorang perempuan primigravida berusia 33 tahun di diagnosa dengan kehamilan pre-term (24 minggu gestasi), janin tunggal hidup intrauterin dengan displasia skeletal tanatoforik tipe 2 via ultrasonografi. Terminasi kehamilan dengan Sectio Caesarea dilakukan atas permintaan pasien setelah mempertimbangkan letalitas janin. Lahir bayi perempuan berat 980 gram, dengan ‘frontal bossing’ (lingkar kepala: 26 cm), kedua telinga rendah, hipertelorisme, eksoftalmos bilateral, leher pendek, ektremitas pendek rizomelik, dan rongga dada kecil (lingkar dada: 17 cm). Bayi segera dipindahkan ke NICU untuk manajemen paska-natal dan observasi. Kondisi bayi stabil selama beberapa jam pertama; namun, ketidakstabilan yang signifikan terjadi setelah itu dan bayi dinyatakan meninggal 10 jam paska kelahiran dikarenakan kegagalan kardiorespirasi. Bayi tidak dilakukan tindakan resusitasi invasif dan pemeriksaan paska kematian atas permintaan pasien. Kesimpulan: Displasia tanatoforik dapat di diagnosa secara primer menggunakan pemeriksaan ultrasonografi (US) dengan tingkat deteksi diagnosis dan prognosis yang tinggi. Meskipun pemeriksaan diagnostik molekular masih menjadi dilema, pemeriksaan ini dapat memprediksi resiko rekurensi pada kehamilan selanjutnya. Walaupun masih merupakan suatu tantangan dalam segi etika dan medikolegal; manajemen ideal perlu mempertimbangkan secara holistik seluruh aspek yang mencakup: ibu, janin, dan paska kelahiran. Kata Kunci: Tatanoforik, Displasia Skeletal, Mutasi FGFR3 Correspondence: Gezta Nasafir Hermawan, Faculty of Medicine, Sam Ratulangi University. Email: gezta.hermawan@gmail.com